AUDIT OPERASIONAL SEKRETARIAT KECAMATAN (STUDI KASUS PADA KECAMATAN GUNUNG PATI KOTA SEMARANG) - Ardian Widiardi,A.Md, 11.05.62.0008; Kartika, Andi (Students Journal of Accounting and Banking, 2017)
Audit of operations in an organization need to be made operational, auditing can be defined over any part of the study was organizations against standard operating procedures and methods applied to an organisation with the purpose to evaluate the efficiency, effectiveness, and economical (3E). Testing SPI intended to collect more detailed information from the program/activity to which work units are assessed to have potential for improved/enhanced Research aims to find out whether performance on the part of the Secretariat was already effective and efficient. The research is qualitative descriptive, namely by observing directly aims to explain or describe a situation, event, object, or whether everything that is related to variables that can be described either with numbers or words, by conducting an analysis of the effectiveness and efficiency of the analysis. The results showed that performance in the planning and evaluation of subag ineffective performance on effective and not financial subag inefficient and performance in General and staffing subag ineffective.Keywords:Â Operational Audits, SPI, Efficiency, Effectiveness